The potential use of citrus juice waste as sources of natural phenolic antioxidants - Ji Hye Kim, Min Young Kim (Journal of Applied Pharmaceutical Science, 2016)
The methanolic extract of citrus juice processing waste was evaluated for its potential applications in medicine or as nutraceutical materials. Determination of total phenolic and flavonoid contents was done by microplate reader, whereas UPLC-mass detection was used for the analysis of individual flavanone (naringin, hesperidin, hesperetin, neohesperedin and narirutin) and flavonol (rutin). In addition, free radicals (DPPH, O2-, H2O2 and NO) scavenging and ferrous ion chelating assays were used to determine the antioxidant capacity. The contents of total phenolic and flavonoid were more prevalent in citrus juice processing waste than the level found in the pulp of citrus fruit. The results of UPLC analyses indicate that citrus juice processing waste was rich in mainly hesperidin and neohesperedin, and it had different flavonoid composition in comparison with the pulp of citrus fruit. The citrus juice processing waste was also found to possess an evident antioxidant capacity. The results showed that citrus wastes could be economic and readily accessible source of natural antioxidants and as a possible food and pharmaceutical supplement.
Keywords: Antioxidant capacity, Citrus juice processing waste, Total phenolic and flavonoid contents.